Efficacy of citalopram and moclobemide in patients with social phobia: Some preliminary findings - Atmaca, M; Kuloglu, M; Tezcan, E; Unal, A (Wiley, 2002)
The efficacy of irreversible and reversible monoamine oxidase inhibitors (MAOIs) in the treatment of social phobia (SP) is well established. Recently, selective serotonin reuptake inhibitors (SSRIs) have been used more frequently. In the present study, the efficacy and side-effect profile of citalopram, an SSRI, and moclobemide, the only MAOI used in Turkey, were compared. The 71 patients diagnosed with SP according to DSM-III-R were randomly assigned to two subgroups; citalopram (n = 36) or moclobemide (n = 35). The study was an 8-week, randomized, open-label, rater-blinded, parallel-group trial. All patients were assessed by Hamilton anxiety rating (HAM-A), Liebowitz social anxiety (LSAS), clinical global impression-severity of illness (CGI-SI) and clinical global impression-improvement (CGI-I) scales. There was a similar percentage of responders (citalopram 75%, n = 27 and moclobemide 74.3%, n = 26), with a > 50% or greater reduction in LSAS total score and ratings of 'very much' or 'much improved' on the CGI-I. None of the patients withdrew from the study. The results of the present study suggest that citalopram has shown promising results in patients with SP. Copyright (C) 2002 John Wiley Sons, Ltd.
Keywords: social phobia; citalopram; moclobemide; efficacy; side-effect